Bevel Engineering in Advanced Packaging - Kim, Keechan; Keovisai, Moty (Proceedings of the IEEE International Interconnect Technology Conference, 2025)
As the semiconductor industry adopts new and more complex advanced packaging schemes, the wafer edge becomes increasingly important in terms of maximizing yield. This paper will provide an overview of packaging applications for both plasma bevel etch and PECVD bevel deposition. Bevel etch has long been used in wafer processing to reduce edge defects but has become instrumental in maintaining wafer edge health for chip-to-wafer and wafer-to-wafer bonding schemes. Bevel deposition replaces multiple process steps with a single annular deposition of Si or C-based film and is being adopted for metal contamination mitigation and edge roll-off compensation prior to wafer-to-wafer bonding.